The radius of baryonic collapse in disc galaxy formation - Kassin, SA; Devriendt, J; Fall, S; Jong, R; Allgood, B; Primack, JR (Oxford University Press, 2012)
In the standard picture of disc galaxy formation, baryons and dark matter receive the same tidal torques, and therefore approximately the same initial specific angular momentum. However, observations indicate that disc galaxies typically have only about half as much specific angular momentum as their dark matter haloes. We argue this does not necessarily imply that baryons lose this much specific angular momentum as they form galaxies. It may instead indicate that galaxies are most directly related to the inner regions of their host haloes, as may be expected in a scenario where baryons in the inner parts of haloes collapse first. A limiting case is examined under the idealised assumption of perfect angular momentum conservation. Namely, we determine the density contrast Delta, with respect to the critical density of the Universe, by which dark matter haloes need to be defined in order to have the same average specific angular momentum as the galaxies they host. Under the assumption that galaxies are related to haloes via their characteristic rotation velocities, the necessary Delta is ~600. This Delta corresponds to an average halo radius and mass which are ~60% and ~75%, respectively, of the virial values (i.e., for Delta = 200). We refer to this radius as the radius of baryonic collapse R_BC, since if specific angular momentum is conserved perfectly, baryons would come from within it. It is not likely a simple step function due to the complex gastrophysics involved, therefore we regard it as an effective radius. In summary, the difference between the predicted initial and the observed final specific angular momentum of galaxies, which is conventionally attributed solely to angular momentum loss, can more naturally be explained by a preference for collapse of baryons within R_BC, with possibly some later angular momentum transfer.